2018
DOI: 10.1021/acsomega.8b00109
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional, Hierarchical Ag-Doped TiO2 Nanocatalysts: Effect of the Metal Oxidation State on the Photocatalytic Properties

Abstract: This paper reports the synthesis of two-dimensional, hierarchical, porous, and (001)-faceted metal (Ag, Zn, and Al)-doped TiO 2 nanostructures (TNSs) and the study of their photocatalytic activity. Two-dimensional metal-doped TNSs were synthesized using the hydrolysis of ammonium hexafluorotitanate in the presence of hexamethylenetetramine and metal precursors. Typical morphology of metal-doped TNSs is a hierarchical nanosheet that is composed of randomly stacked nanocubes (dimensions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…As expected from previous works on similar Ag-doped TiO 2 nanoparticles [1][2][3][4][5], the diffraction peaks associated with Ag were not easily observed. Similar to these prior works, the pres- ence of Ag did not cause changes in the TiO 2 anatase crystalline structure and no significant high intensity peaks related to fcc Ag were observed.…”
Section: Xrd Of Tio 2 and Ag-doped Tio 2 Nanoparticlessupporting
confidence: 80%
“…As expected from previous works on similar Ag-doped TiO 2 nanoparticles [1][2][3][4][5], the diffraction peaks associated with Ag were not easily observed. Similar to these prior works, the pres- ence of Ag did not cause changes in the TiO 2 anatase crystalline structure and no significant high intensity peaks related to fcc Ag were observed.…”
Section: Xrd Of Tio 2 and Ag-doped Tio 2 Nanoparticlessupporting
confidence: 80%
“…Recent studies have shown that the improvement of the photocatalytic properties of the TiO 2 doped with transition metals can also be seen in terms of modification of density of state of the VB that includes the change in the d-orbital shape and broadening. 65…”
Section: Resultsmentioning
confidence: 99%
“…By comparison, the photocatalytic activity of the Ag + ‐doped sample was higher than that of Cu 2+ one. Furthermore, Ag atoms were also doped into other 2D TNMOs to improve the photocatalytic activity, such as 2D TiO 2 nanocatalyst, K 4 Nb 6 O 17 , RbLaNb 2 O 7 , and RbA 2 Nb 3 O 10 (A = Ca and Sr) …”
Section: Enhanced Photocatalytic Activity With Modificationmentioning
confidence: 99%